Long-term prediction of prostate cancer up to 25 years before diagnosis of prostate cancer using prostate kallikreins measured at age 44 to 50 years. - Lilja, H; Ulmert, D; Björk, T; Becker, C; Serio, A; Nilsson, J; Abrahamsson, P; Vickers, A; Berglund, G (2007)
PURPOSE: We examined whether prostate-specific antigen (PSA) forms and human kallikrein 2 (hK2) measured at age 44 to 50 years predict long-term risk of incident prostate cancer. METHODS: From 1974 to 1986, 21,277 men age 50 years in Malmö, Sweden, enrolled onto a cardiovascular study (74% participation). The rate of PSA screening in this population is low. According to the Swedish Cancer Registry, 498 were later diagnosed with prostate cancer. We measured hK2, free PSA, and total PSA (tPSA) in archived blood plasma from 462 participants later diagnosed with prostate cancer and from 1,222 matched controls. Conditional logistic regression was used to test for association of prostate cancer with hK2 and PSA forms measured at baseline. RESULTS: Median delay between venipuncture and prostate cancer diagnosis was 18 years. hK2 and all PSA forms were strongly associated with prostate cancer (all P < .0005). None of the 90 anthropometric, lifestyle, biochemical, and medical history variables measured at baseline was importantly predictive. A tPSA increase of 1 ng/mL was associated with an increase in odds of cancer of 3.69 (95% CI, 2.99 to 4.56); addition of other PSA forms or hK2 did not add to the predictive value of tPSA. tPSA remained predictive for men diagnosed > or = 20 years after venipuncture, and the predictive value remained unchanged in an analysis restricted to palpable disease. CONCLUSION: A single PSA test at age 44 to 50 years predicts subsequent clinically diagnosed prostate cancer. This raises the possibility of risk stratification for prostate cancer screening programs.